Prevalence of hearing loss and factors associated with hearing loss in Ethiopia: findings from the 2023 National Ethiopia Hearing Survey - Tolesa Diriba Biratu; Alene Meshesha; Uta Fröschl; Michael Kebede; Yoseph Worku; Fufa Hunduma (BMJ Open)
Objectives To assess the prevalence and associated factors of hearing loss in Ethiopia, considering socioeconomic conditions, regional variations and age-related impacts.Design Nationwide cross-sectional survey.Setting Data were collected from 2 February to 10 June 2023, covering all regions of Ethiopia except Tigray (due to security concerns).Participants A sample of 3000 households and 7061 individuals aged 5 years and above was selected using a multistage sampling procedure. Eligible participants had resided in the area for at least 6 months. Exclusions included visitors, critically ill individuals and those with communication difficulties.Outcome measures Hearing loss was defined as an average hearing threshold >20 dB in the better ear at frequencies of 0.5 kHz, 1 kHz, 2 kHz and 4 kHz, measured using pure-tone audiometry. Logistic regression analysis was performed to determine factors associated with hearing loss.Results The overall prevalence of hearing loss among individuals aged 5+ years was 18.4%. The prevalence was 8.1% among children aged 5–14 years and 73.7% among adults aged 60+ years. Factors significantly associated with hearing loss included being over 60 years old (adjusted OR (AOR)=51.41; 95% CI 36.95, 71.53), having no formal education (AOR=2.12; 95% CI 1.47, 3.08), ear discharge (AOR=3.01; 95% CI 2.07, 4.38), wax presence (AOR=1.92; 95% CI 1.53, 2.40), and tympanic membrane abnormality (AOR=17.17; 95% CI 12.27, 24.02). Participants from the Harari (AOR=3.25; 95% CI 1.85, 5.72) and Somali (AOR=2.37; 95% CI 1.49, 3.77) regions were more likely to experience hearing loss compared with those from other regions.Conclusions Hearing loss is highly prevalent in Ethiopia, influenced by both modifiable and non-modifiable factors. Regional disparities in hearing loss suggest a need for targeted interventions. Evidence-based policies and strategies are essential to reduce ear diseases, improve hearing care services, and address disparities in hearing health across regions.